Formulas and algorithms of antimagic labelings of some helm related graphs. (3rd March 2016) - Krishnaa, A.
Abstract: This paper presents algorithms, formulas and proofs for antimagic labelings for some graphs which are related in structure with helms. The labelings obtained are not only antimagic but also exhibit much regularity of patterns in the behaviour of the induced vertex labels.